Evaluasi Program Pembelajaran - Gunawan, Imam (Jurnal Pendidikan, 2011)
Mastery in teaching IPS SD (Social Science of Elementary School) at high classes has become obligatory for elementray school teacher training program graduates. This subject requires them to integrate factual social themes in the basis of social sciences with the mind-set of elementaru school students at high classes. Lesson study program has been launched during the last semester, inducing steps of plan, do and see. Collaborative teaching model has factually promoted a new teaching experience even for lecturers owing to the performance development of lecturers, which hopefully encourages the students learning appreciation against Social Science of Elementary School subject. This research is intended to have an out-look on the develpment of teaching performance for lecturers and encouragement of learning appreciation for students in Social Science of Elementary School.Keywords: Lesson study, teaching Social Science of Elementary School at high classes